PREVENTION AND MANAGEMENT OF POSTOPERATIVE DELIRIUM IN ANESTHESIOLOGY AND REANIMATOLOGY: INTERNATIONAL STANDARDS AND 2025 SCIENTIFIC APPROACHES (European Journal of Interdisciplinary Research and Development, 2025)
Postoperative delirium (POD) is one of the most common neurological complications in anesthesiology and reanimatology, prolonging hospital stay, increasing mortality risk, and raising healthcare costs. This article provides a detailed analysis of risk factors, screening tools, preventive strategies, pharmacological and non-pharmacological treatments, and monitoring in the resuscitation phase of POD, based on the 2025 guidelines from the European Society of Anaesthesiology and Intensive Care (ESAIC), American Society of Anesthesiologists (ASA), American Geriatrics Society (AGS), and World Health Organization (WHO). The work fully complies with the requirements of the Higher Attestation Commission of Uzbekistan (OAK), incorporating original analysis, empirical evidence, statistical data, clinical examples, and nationally adapted practical recommendations. Research findings indicate that multicomponent prevention programs can reduce POD incidence by 35–50%, hospital stay by 1.8–3.2 days, and mortality risk by 22%, but challenges such as resource constraints, educational gaps, and lack of databases must be addressed.